MODIFIED THRESHOLD FOULING MODEL FOR CRUDE OILS - SHETTY, NITIN (2016)
The existing threshold fouling models predict an increase in initial fouling rates with an increase in film temperature. It has been observed by a few researchers that the initial fouling rates decrease for an increase in the film temperature due to an increase in bulk temperature. The existing threshold fouling models fail to predict this phenomenon. The limitation of the existing threshold fouling models makes them inappropriate when the bulk temperature changes as in the crude preheat train of a refinery. A series of experiments were carried out to investigate the fouling characteristics of crude oils A, B and C at different bulk and surface temperatures, keeping flow velocity and heat flux constant in a pilot-scale recirculation flow loop called Annular Flow Fouling Research Unit (AFFRU).